A step on the messy path to alignment: Developing the aboriginal and torres strait islander intercultural capability framework - Goerke, Veronica; Taylor, Kate; Kickett, Marion (2015)
Like many other Australian universities, Curtin University identifies intercultural capabilities in its list of graduate attributes. Within this mandate, Curtin is increasingly foregrounding the need for graduates to develop Indigenous cultural capabilities. It is widely recognised that in order to develop these capabilities in graduates, educators at the interface need to embody these capabilities. Similarly, what has become increasingly clear is that it is not only educators but staff across the university that need intercultural skills and understanding in order to move towards a 'decolonised' academic environment that will truly support the development of cultural capabilities in graduates. Within the undergraduate curriculum, one of the core principles of developing cultural capabilities is that they are a journey, requiring students to engage with material through a graduated, progressive learning experience. At Curtin, the importance of mirroring this graduated learning journey for staff has been recognized, and in an effort to move from theory towards actualising staff cultural capabilities, the Indigenous Cultural Capabilities Framework' (ICCF) is currently being developed (referred to by these authors as the Aboriginal and Torres Strait Islander Cultural Capabilities Framework). The Curtin University ICCF aims to map pathways that progress staff in developing cultural capabilities, as well as the measures with which the achievement of these capabilities are assessed. While programs and models to develop staff intercultural capabilities through professional development activities is not new, what appears to be unique with Curtin's ICCF is its attempt to implement a graduated professional developmental program for all levels of staff across a large university. At the conference we discussed, the somewhat messy process of developing and implementing the ICCF, and we also shared a draft of part of the framework.